2013
DOI: 10.1590/s1413-35552012005000124
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity study of the Kinesthetic and Visual Imagery Questionnaire in individuals with Multiple Sclerosis

Abstract: ObjectiveMotor imagery (MI) has been recently considered as an adjunct to physical rehabilitation in patients with multiple sclerosis (MS). It is necessary to assess MI abilities and benefits in patients with MS by using a reliable tool. The Kinesthetic and Visual Imagery Questionnaire (KVIQ) was recently developed to assess MI ability in patients with stroke and other disabilities. Considering the different underlying pathologies, the present study aimed to examine the validity and reliability of the KVIQ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 20 publications
3
27
0
2
Order By: Relevance
“…The maximum KVIQ-10 total scale is 50 points, with 25 points in each subscale, and higher scores representing higher levels of MI ability. The KVIQ-10 has been attributed excellent validity and reliability in people with stroke [ 55 ] and MS [ 57 ]. For this study, the validated German version of the KVIQ-10 was used, the KVIQ-G-10 [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The maximum KVIQ-10 total scale is 50 points, with 25 points in each subscale, and higher scores representing higher levels of MI ability. The KVIQ-10 has been attributed excellent validity and reliability in people with stroke [ 55 ] and MS [ 57 ]. For this study, the validated German version of the KVIQ-10 was used, the KVIQ-G-10 [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…One of the most popular and commonly used questionnaires is the revised version of the Movement Imagery Questionnaire [MIQ-R], that is an appropriate instrument for the assessment of VI and KI motor imagery ( 28 ). In order to be used in rehabilitation practice, the previous version of MIQ-R was revised ( 29 , 30 ), and its validity was confirmed ( 29 , 30 , 31 , 32 ). Since both the incidence and prevalence of diseases such as cardiovascular, neuro-musculo-skeletal increase with age ( 5 , 33 ) the longer life expectancy that is being faced globally will result in an increase rate of disabled individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The present study, therefore, not only expands the evidence base for the psychometric properties of the KVIQ to the Brazilian-Portuguese context, but further enhances the specific evidence base for KVIQ data in persons with stroke. As such, it adds an important component to the literature reporting reliability and consistency of the KVIQ 20 or its subscales in participants with multiple sclerosis 23 , Parkinson´s disease 9 and a mixed sample of participants with stroke, brain tumors, multiple sclerosis or Parkinson's disease 24 . These previous studies in populations with different neurological conditions reported intra-rater reliability, not inter-rater reliability.…”
Section: Discussionmentioning
confidence: 99%